CORPORATE CIVIL LIABILITY FOR ENVIRONMENTAL POLLUTION FROM THE PERSPECTIVE OF INDONESIAN CIVIL LAW - Trianto; Hendrawan, Daniel; Rahmat, Diding (JILPR Journal Indonesia Law and Policy Review, 2026)
Environmental pollution caused by corporations has serious impacts on communities and ecosystems. Civil lawsuits are one of the legal mechanisms used to hold corporations accountable and obtain compensation for the losses caused. This study examines how the mechanisms of evidence and compensation are applied in civil cases against corporations responsible for environmental pollution in Indonesia. Proving environmental cases is not always straightforward, as it requires complex scientific evidence and the involvement of experts. Therefore, the principle of strict liability or absolute liability under Law No. 32 of 2009 on the Protection and Management of the Environment serves as an important legal basis for enforcing environmental justice. Compensation is not only intended to compensate victims for their losses but also as an effort to restore the environment. This study emphasizes the importance of strengthening the capacity of law enforcement officials, enhancing the role of the community, and optimizing environmental courts to ensure that civil litigation mechanisms operate effectively and fairly.